anonymous
  • anonymous
The vertex of the graph of a quadratic functon is (3,1) and the y intercept is (0,10). What is the equations of the function?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
\[\text{Let } f(x) = k(x-a)^2 + c\] (general quadratic with square completed) (3,1) is a minimum => a = .... and c = .... When x = 0, f(x) = 10, so k = ... We can now expand and find the solution in the form f(x) = px^2 + qx + r
anonymous
  • anonymous
No idea what to do after that. But thank you!
anonymous
  • anonymous
Well, if a quadratic is at a minimum, x = a in the bracket (as the bracket is >= 0 for all x) So the only value is the + c This occurs at the point x = 3, y = 1, so we can deduce that the "a" = 3, and the c = 1 => f(x) = k(x-3)^2 + 1 When x = 0, f(x) = 10. So k* (-3)^2 + 1 = 10 -> 9k + 1 = 10 -> k = 1 So f(x) = (x-3)^2 + 1, which we could expand (if we want) to f(x) = ....

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
¬_¬
anonymous
  • anonymous
I didn't get it correct :/
anonymous
  • anonymous
What answer did you give?
anonymous
  • anonymous
(x-3)^2 + 1 = x^2 - 6x + 10, which is the answer
anonymous
  • anonymous
I don't remember! :/ it's an onlne class so I can't go back and change my anwers.

Looking for something else?

Not the answer you are looking for? Search for more explanations.